Optimizing the Heck–Matsuda Reaction in Flow with a Constraint-Adapted Direct Search Algorithm - Cortes-Borda D. Daniel; Kutonova K. V. Ksenia Valentinovna; Corentin J. Jamet; Trusova M. E. Marina Evgenievna; Zammattio Francoise; Truchet Charlotte; Rodriguez-Zubiri Mireia; Felpin Francois-Xavier (2016, 2016)
Title screen